Conflict-Elicited Negative Evaluations of Neutral Stimuli: Testing Overt Responses and Stimulus-Frequency Differences as Critical Side Conditions - Goller, Florian; Kroiss, Alexandra; Ansorge, Ulrich (Frontiers in Psychology, 2019)
Prior research has shown that a stimulus signaling a conflict (such as an incongruent Stroop stimulus) as a prime can elicit more negative evaluations of an otherwise neutral and unrelated stimulus as a target. Yet, there are many side conditions that could at least partly be responsible for such effects like the frequencies of congruent and conflicting stimuli or overt responses to the conflicting stimuli. Here, we tested the influences of stimulus frequencies and overt responses on the strength of this priming effect. In four experiments, we demonstrate that overt responses in-between prime and target do not delete the conflict-elicited evaluation effect (Experiments 1a vs. 1b), while an overall higher frequency of conflicting trials (Experiment 2a) and an overall lower frequency of congruent trials (Experiment 3) can both abolish the priming effect. In contrast, a higher frequency of specific conflicting conditions was ineffective (Experiment 2b). Together, our results confirm that conflict is indeed the origin of the priming of negative evaluations.